THE INFLUENCE OF THE HISTORY OF ISLAMIC CIVILISATION IN VARIOUS FIELDS - Wardatul Ilmiah; M. Makhrus Ali (Adisam Publisher, 2026)
Islamic civilisation had a major impact on the development of science, technology, art and culture. In the field of science, Muslim scholars such as Al-Khwarizmi and Ibn Sina made significant breakthroughs that formed the basis of modern science. Technology flourished with innovations in irrigation, navigation and various mechanical devices that supported daily life as well as global exploration. Islamic art and culture offered great contributions through magnificent architecture, beautiful calligraphic art, and literary and musical works that enriched global culture, demonstrating the harmony between aesthetics and spirituality that is distinctive in Islamic culture.